Integrasi Pendidikan Karakter Dalam Pembelajaran Kelas II Sekolah Dasar - Hudayana, Dewi; Sururuddin, Muhammad; Husni, Muhammad (Ta’dib: Jurnal Pendidikan Islam dan Isu-Isu Sosial, 2025)
This study aims to describe the integration of character education in the learning process of second-grade students at SD Negeri Petemon, Lendang Are Village, Kopang District. The research employed a descriptive qualitative method with the subjects being the second-grade teacher, 25 students, and the principal. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model. The results of the study show that character education is integrated through thematic learning, teacher role-modeling, and daily habituation. The dominant character values developed are discipline, responsibility, religiosity, cooperation, and honesty. Supporting factors include parental involvement, local cultural values, and a conducive school environment. The main obstacles are limited time, insufficient teacher skills, and varied student motivation. These findings emphasize the importance of synergy among teachers, parents, and the community to strengthen character education in elementary schools.